Methods for Establishment and Maintenance of Germ-Free Rat Models - Qv, Lingling; Yang, Zhenggang; Yao, Mingfei; Mao, Sunbing; Li, Yongjun; Zhang, Jia; Li, Lanjuan (Frontiers in Microbiology, 2020)
Numerous studies have demonstrated that the gut microbiota plays a vital role in human health and disease development. Although the number of studies on host-microbiota interactions have increased in recent years, the underlying pathogenesis of dysbiosis-related diseases are still largely unknown. Germ-free (GF) rodent models, with the animals housed in sterile isolators and completely free of microbiota, are useful tools to advance our understanding of host-microbiota relationship in vivo. Although protocols concerning the establishment and maintenance of GF mouse models have previously been reported, the establishment, maintenance and monitoring of GF rodents are labor-intensive, tedious and take experience and skills. The aim of our study was to establish a GF rat model for the following microbiota-related researches and provide an easy-to-use protocol for the establishment and maintenance of GF rat model in detail, including steps to set up the isolator, sterilize the flexible isolator bubble, import food, water and other supplies, and methods to acquire newborn GF rats, hand rearing of suckling GF rats and reproduction of GF offspring. During the hand feeding period, the body weight of suckling GF rats was weighed once a day to ascertain the amount of artificial milk was given. Based on our results, the body weight of suckling GF rats decreased one week after birth and then began to increase. Methods for verifying the quality of the model like assessing the sterile status of the rat colony are also described. Moreover, possible difficulties and challenges, especially during gavage, and suggestions to avoid contamination will be discussed. The protocol presented will facilitate the establishment of GF rat models and downstream microbiota-related researches.